Swedish youth labour market policies revisited - Anders Forslund; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2006)
The paper studies the efficiency of Swedish labour market policies for young workers. Using age discontinuities which define which policy regime an individual is covered by we present quasi-experimental evidence on the relative efficiency of different policy regimes currently in use. Results suggest that youth policies are more effective than the policies covering adult unemployed. The effects mainly appear early in the unemployment spell; we find no evidence of positive long run effects. To uncover which part of the policies that accounts for the positive effect, we use matching techniques to study the relative efficiency of youth programmes and general adult programmes which are available also for the young. The results indicate that youth programmes are significantly less effective than adult oriented programmes. Overall, the evidence thus suggest that youth policies speed up the transition from unemployment to jobs either due to pre-programme deterrence effects or because of more intense job search support from the public employment services before the programmes.
Keywords: J64; J68; 330; Youth unemployment; program evaluation; pre-program effects; Junge Arbeitskräfte; Jugendarbeitslosigkeit; Arbeitsmarktpolitik; Schätzung; Schweden